3.5 Year Monitoring of 225 GHz Opacity at the Summit of Greenland. (21st December 2016) - Matsushita, Satoki; Asada, Keiichi; Martin-Cocher, Pierre L.; Chen, Ming-Tang; Ho, Paul T. P.; Inoue, Makoto; Koch, Patrick M.; Paine, Scott N.; Turner, David D.
Abstract: We present the 3.5 years monitoring results of 225 GHz opacity at the summit of the Greenland ice sheet (Greenland Summit Camp) at an altitude of 3200 m using a tipping radiometer. We chose this site as our submillimeter telescope (Greenland Telescope) site, because conditions are expected to have low submillimeter opacity and because its location offers favorable baselines to existing submillimeter telescopes for global-scale Very Long Baseline Interferometry. The site shows a clear seasonal variation with the average opacity lower by a factor of two during winter. The 25%, 50%, and 75% quartiles of the 225 GHz opacity during the winter months of November through April are 0.046, 0.060, and 0.080, respectively. For the winter quartiles of 25% and 50%, the Greenland site is about 10%–30% worse than the Atacama Large Millimeter/submillimeter Array (ALMA) or the South Pole sites. Estimated atmospheric transmission spectra in winter season are similar to the ALMA site at lower frequencies ( < 450 GHz), which are transparent enough to perform astronomical observations almost all of the winter time with opacities < 0.5, but 10%–25% higher opacities at higher frequencies ( > 450 GHz) than those at the ALMA site. This is due to the lower altitude of the Greenland site and the resulting higher line wing opacity from pressure-broadened saturated water lines in addition to higher dry air continuum absorption at higher frequencies. Nevertheless, half of the winter time at the Greenland Summit Camp can be used for astronomical observations at frequencies between 450 GHz and 1000 GHz with opacities < 1.2, and 10% of the time show > 10 % transmittance in the THz (1035 GHz, 1350 GHz, and 1500 GHz) windows. Summer season is good for observations at frequencies lower than 380 GHz. One major advantage of the Greenland Summit Camp site in winter is that there is no diurnal variation due to the polar night condition, and therefore the durations of low-opacity conditions are significantly longer than at the ALMA site. Opacities lower than 0.05 or 0.04 can continue for more than 100 hr. Such long stable opacity conditions do not occur as often even at the South Pole; it happens only for the opacity lower than 0.05. Since the opacity variation is directly related to the sky temperature (background) variation, the Greenland Summit Camp is suitable for astronomical observations that need unusually stable sky background.